Nonapoptotic functions of caspases: caspases as regulatory molecules for immunity and cell-fate determination. - Kuranaga, E.; Miura, M. (Trends in Cell Biology, 2007)
Caspases are a family of cysteine proteases that are highly conserved in multicellular organisms and function as central regulators of apoptosis. Recent investigations in Caenorhabditis elegans, Drosophila and mice suggest that caspases also function as regulatory molecules for immunity and cell-fate determination. Here, we review genetic studies of nonapoptotic functions of caspases and discuss the regulatory mechanisms of caspases for executing nonapoptotic functions.